Building productive and innovative businesses with BMC strategies to increase MSME income (Case study of MIP animal feed shop MSMEs in Buduran village – Sidoarjo) - Farochah; Rahmawati, Imelda Dian (Apollo: Journal of Tourism and Business, 2025)
The objectives in this study, namely 1) to build a productive and innovative business with the BMC strategy in the MIP Animal Feed Shop MSMEs with a nine-element business model canvas approach, namely customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, cost structure. 2) to design the business model of the Animal Feed Shop based on the Business Model Canvas at this time and after experiencing improvements.   This research method is a qualitative analysis consisting of descriptive analysis and SWOT analysis.  The result of this study is that the UMKM MIP Animal Feed Shop has fulfilled all nine elements of the business model canvas.   However, the current business model at the MIP Animal Feed Shop MSME still has weaknesses, thus creating strategies resulting from improvements to the business model canvas such as product diversification, namely by buying livestock products from farmers such as eggs and chickens, sales using e-commerce or social media, increasing capital and the number of employees so as to increase the internal revenue of the Buduran Animal Feed Shop and can also increase the income of MSMEs in the Sidoarjo area.